Hydrogen sulfide regulates circadian-clock genes in C(2)C(12) myotubes and the muscle of high-fat-diet-fed mice - Parsanathan, Rajesh (Arch Biochem Biophys, 2019)
Hydrogen sulfide (H(2)S) is an endogenous novel gasotransmitter which is implicated in the pathophysiology of the metabolic syndrome. Core clock genes (CCG) and its controlled genes disruption is implicated in the progression of metabolic syndrome. We examined whether H(2)S has any effect on CCG in the skeletal muscle of mice fed a high-fat diet (HFD) and in myotubes. In the muscle of HFD-mice, the expression of H(2)S biosynthesis enzyme genes (CSE, CBS, and 3-Mpst) along with antioxidant genes (GCLC, GCLM, GSS, and GSR) involved in GSH biosynthesis and recycling were reduced significantly, but the oxidative stress (OS) increased. Expression of the CCG (Bmal1, Clock, RORα, Cry2, Per2) and clock-controlled genes (PPARγ, PGC-1α, RXRα) was downregulated, whereas the levels of PPARα mRNA were upregulated. Similar to that in the muscle of HFD-mice, in vitro myotubes exposed to high glucose or palmitate to mimic metabolic syndrome, showed an increased OS and decreased in CSE mRNA, H(2)S production and CCG mRNA levels were also downregulated.TNF and MCP-1 treatment on the myotubes was similar to that observed in HFD-muscle, with that the Rev-erbα mRNA was upregulated. Inhibition (siRNA/pharmacological inhibitors) of both CSE and GCLC (the rate-limiting enzyme in GSH biosynthesis) decreased H(2)S, and increased OS; Bmal1 and Clock mRNA levels were downregulated, while Rev-erbα increased significantly in these conditions. CSE KD myotubes were post-treated with an H(2)S donor partially restored the mRNA levels of core clock genes. These findings report that the deficiencies of H(2)S/GSH impair expression of CCG and treatment with H(2)S donor or GSH precursor exert a positive effect over CCG. Thus, suggest that H(2)S as a new endogenous factor for regulating circadian clock, and its donors could provide a novel chronopharmacological therapy to manage metabolic disorders.